PENDAMPINGAN HAK-HAK PEREMPUAN DAN ANAK PASCA PERCERAIAN - Sholeh, Aziz; Rachmat Gumelar, Dian; Tsamrotul Fuadah, Aah (CIC Lembaga Riset dan Konsultan Sosial, 2019)
This article aims to provide knowledge and assistance as a form of protection for the rights of women and children after divorce, as well as to determine the supporting factors and obstacles to their fulfillment. The approach used is participatory action research (PAR). The way this is done is by providing counseling and legal assistance. The results showed that effectively assisted subjects were able to: (a) Identify social problems in their environment, especially those related to household; (b) Knowing the rights as wife and ex-wife and the rights of children; (c) Share the experiences they get from life; (d) Solve problems with solutions they think are strategic; (e) They know very little that they need help and empowerment. Furthermore, the service team assisted the litigation process at the Soreang Religious Court and the Sumedang Religious Court. In practice, the fulfillment of the rights of women and children after divorce is supported by various factors. As a supporting factor for the fulfillment of the rights of women and children after divorce, among others (1) the good faith of the husband, (2) the decision of the panel of judges that includes the husband's obligations to his ex-wife in the event of a divorce, and (3) the husband has income and / or assets sufficient to meet the demands of the obligation. While the causative factors that hinder the protection of women's rights after divorce, especially in the case of divorce, include: (1) the absence of clear and firm rules against husbands who do not carry out the pledge of divorce, which creates legal uncertainty, (2) decisions that cannot be executed. (3) low legal awareness and legal knowledge in the community.